2021
DOI: 10.1053/j.jrn.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hyperphosphatemia in End-Stage Renal Disease: A New Paradigm

Abstract: Bone and mineral metabolism becomes dysregulated with progression of chronic kidney disease (CKD), and increasing levels of parathyroid hormone serve as an adaptive response to maintain normal phosphorus and calcium levels. In end-stage renal disease, this response becomes maladaptive and high levels of phosphorus may occur. We summarize strategies to control hyperphosphatemia based on a systematic literature review of clinical trial and real-world observational data on phosphorus control in hemodialysis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 99 publications
1
48
0
7
Order By: Relevance
“…Hyperphosphatemia is a common complication observed among patients receiving maintenance dialysis, and is associated with dystrophic calcification (affecting vasculature and heart valves), fractures, cardiovascular mortality and all-cause mortality (1)(2)(3). Current approaches to hyperphosphatemia managementincreasing hemodialysis session length or frequency, dietary phosphate restriction and phosphate binder therapyare difficult to implement (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperphosphatemia is a common complication observed among patients receiving maintenance dialysis, and is associated with dystrophic calcification (affecting vasculature and heart valves), fractures, cardiovascular mortality and all-cause mortality (1)(2)(3). Current approaches to hyperphosphatemia managementincreasing hemodialysis session length or frequency, dietary phosphate restriction and phosphate binder therapyare difficult to implement (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Kadar PTH yang berlebihan selanjutnya menyebabkan mobilisasi kalsium dari tulang dan osteitis fibrosa. 6,9,18 Progresivitas penurunan fungsi ginjal juga menyebabkan penurunan responsivitas reseptor vitamin D (VDR) pada kelenjar paratiroid yang berakibat peningkatan produksi PTH lebih lanjut. Kondisi ini juga menurunkan ekspresi reseptor peka kalsium pada kelenjar paratiroid yang menginduksi terjadinya hiperplasia kelenjar.…”
Section: Abnormalitas Parameter Biokimiaunclassified
“…Data suggest that nocturnal hemodialysis more effectively lowers serum phosphate than conventional hemodialysis (from 1.78 to 1.44 mmol/L [5.5 to 4.5 mg/dL]). 34 , 35 In the Nocturnal trials, patients receiving 6x-weekly sessions experienced a relative decrease of 0.40 mmol/L (1.2 mg/dL) in mean serum phosphate compared with patients receiving 3x-weekly sessions. Similarly, the Daily trial demonstrated that patients receiving 6x weekly sessions experienced a relative decrease of 0.15 mmol/L (0.5 mg/dL) in mean serum phosphate levels compared with patients receiving 3x weekly sessions.…”
Section: Strategies To Manage Hyperphosphatemiamentioning
confidence: 99%
“…Aluminum-hydroxide has a high ionic binding affinity, low pill burden, and is relatively inexpensive. 34 However, in the 1970s an increasing number of dialysis patients experienced severe aluminum intoxication. While dialysis fluid contamination by aluminum was identified as the culprit, intoxication with aluminum-containing phosphate binders was later reported in non-dialyzed patients.…”
Section: Strategies To Manage Hyperphosphatemiamentioning
confidence: 99%